2015
DOI: 10.1007/s00415-015-7990-2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive supranuclear palsy: progression and survival

Abstract: Progressive supranuclear palsy (PSP) is a progressive neurodegenerative disorder characterized by postural instability and falls, vertical supranuclear gaze palsy, parkinsonism with poor levodopa response, pseudobulbar palsy, and frontal release signs. The natural history of the disease has been previously described. However, the time frame of appearance of clinical milestones and how these symptoms may relate to survival in PSP are unknown. The primary objective was to determine the prevalence of symptoms at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 45 publications
7
46
1
Order By: Relevance
“…Few studies investigated the association between urinary incontinence and survival time, though it was one of the prevalent autonomic symptoms in PSP[5, 23,24]. In our study, we found the association between incontinence and survival and institutionalization in univariate model, but the association became negative in multivariate model.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Few studies investigated the association between urinary incontinence and survival time, though it was one of the prevalent autonomic symptoms in PSP[5, 23,24]. In our study, we found the association between incontinence and survival and institutionalization in univariate model, but the association became negative in multivariate model.…”
Section: Discussionsupporting
confidence: 44%
“…Published studies found that the median survival time of patients with PSP-F was similar with PSP-RS and its cumulative mortality after 5 years was mildly higher than PSP-RS [25][26][27]. The dementia and frontal symptoms, the most common features in PSP-F, were also regarded associated with earlier death [4,23]. A recently published study found cognitive impairment in PSP, especially executive dysfunction, was associated with severity of PSP-related tau pathology in autopsy-confirmed PSP patients, which might explain the association with poorer prognosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations and a drift in psychiatric symptoms are usually regarded as diagnostic features of DLB . These are not frequent in clinically diagnosed PSP . Still, hallucinations have been noted in 6% of an autopsy‐verified series of PSP .…”
Section: Lessons From Atypical Casesmentioning
confidence: 99%
“…For instance, metabolic enzyme aconitase plays an important role in mitochondrial physiology, and its attenuated activity is a contributing factor in progressive supranuclear palsy (PSP) (Park et al 2001) and influences the progression of Huntington's disease (HD) (Tabrizi et al 1999). PSP is characterized by progressive neurodegeneration resulting in postural instability and increased risk of falling, parkinsonism and pseudobulbar palsy (Arena et al 2016). The disease has late onset and commences with the symptoms of motor dysfunction (Boeve 2012).…”
Section: Lon Proteasementioning
confidence: 99%